Country of origin labeling for complex supply chains: the case for labeling the location of different supply chain links. (23rd February 2016) - Bienenfeld, Jason M.; Botkins, Elizabeth R.; Roe, Brian E.; Batte, Marvin T.
Abstract: We investigate the value of a country of origin label (COOL) that separately identifies the geographic location of different stages in a food product's supply chain. We estimate the willingness‐to‐pay (WTP) of U.S. consumers for a packaged cereal product where the key grain ingredient may be grown in one country and processed in a second country (multicountry supply chain) and compare it to equivalent products that have both stages located in a single country. We find consumer WTP for products with single‐country and multicountry supply chains are statistically different, meaning that simplifying a multicountry label by listing only the country where the ingredients are grown or only the country where the ingredients are processed can result in different consumer values. We also find that for countries with a poor quality reputation, consumers respond more negatively when that country has the "last touch" than when that country's involvement is limited to upstream supply chain links.